Antibodies to Full-Length Agrin Protein in Chinese Patients With Myasthenia Gravis - Wang, Shumin; Yang, Haonan; Guo, Rongjing; Wang, Lulu; Zhang, Yingna; Lv, Jie; Zhao, Xue; Zhang, Jing; Fang, Hua; Zhang, Qingyong; Zhang, Yunke; Yang, Junhong; et al. (Frontiers in Immunology, 2021)
This study aimed to establish a cell-based assay (CBA) for the detection of agrin antibodies (Agrin-Ab) to explore the clinical features of agrin antibody-positive Chinese patients with myasthenia gravis (Agrin-MG). We developed a CBA based on the human full-length agrin protein expressed in HEK293T cells for the reliable and efficient detection of Agrin-Ab. Clinical data and serum samples were collected from 1948 MG patients in 26 provinces in China. The demographic and clinical features of Agrin-MG patients were compared with those of other MG patient subsets. Eighteen Agrin-MG cases were identified from 1948 MG patients. Nine patients were Agrin-Ab positive, and nine were AChR-Ab and Agrin-Ab double-positive (Agrin/AChR-MG). Eleven (61.11%) patients were males older than 40 years of age. The initial symptom in 13 (81.25%) cases was ocular weakness. Occasionally, the initial symptom was limb-girdle weakness (two cases) or bulbar muscle weakness (one case). Agrin-MG patients demonstrated slight improvement following treatment with either acetylcholinesterase inhibitor or prednisone; however, the combination of the two drugs could effectively relieve MG symptoms. In China, Agrin-MG demonstrated seropositivity rates of 0.92%. These patients were commonly middle-aged or elderly men. The patients usually presented weakness in the ocular, bulbar, and limb muscles, which may be combined with thymoma. These patients have more severe diseases, although the combination of pyridostigmine and prednisone was usually effective in relieving symptoms.